RELIABILITY ASSESSMENT OF OUTDOOR LIGHTING - , А. В., П. П., В. П. (Municipal economy of cities. Series: «Economy science», 2013)
We consider the reliability of outdoor lighting and improve the efficiency of the lighting of the complex.